Policy analysis of regional tax surtaxes and their impact on fiscal autonomy and public service quality - Aditiya Rizqi Febriansah; Mohamad Rafli Dzakwan; Muhammad Solehudin (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2025)
Background: This study examines the effectiveness of the Motor Vehicle Tax/Pajak Kendaraan Bermotor (PKB) surcharge (opsen) as a fiscal instrument to enhance regional financial independence and improve public service delivery in West Java Province. Introduced as part of Indonesia’s fiscal decentralization framework, the opsen aims to optimize local revenue generation while strengthening provincial autonomy in managing essential public services such as education, transportation, and environmental management. Methods: Using a qualitative descriptive approach supported by secondary data from provincial budget reports, tax realization statistics, and regulatory documents, this paper analyzes the structure of PKB and BBNKB revenues, the contribution of the opsen to Regional Own-Source Revenue/Pendapatan Asli Daerah (PAD), and its alignment with regional expenditure priorities. Findings: The study finds that West Java has successfully utilized the opsen to expand its fiscal capacity, evidenced by consistent growth in PAD and an improved fiscal independence ratio. Nevertheless, challenges remain, including disparities in taxpayer compliance, uneven regional revenue performance, and the need for stronger integration between tax policy and service delivery outcomes. The analysis suggests that the opsen can serve as an effective public finance strategy when supported by transparent revenue management, strengthened digital tax administration, and targeted spending on high-impact public sectors. Conclusion: The study concludes that optimizing the opsen mechanism is crucial for reinforcing fiscal resilience, promoting accountable governance, and ensuring that additional tax revenue translates into measurable improvements in public services. Novelty/Originality of this article: This study contributes to the fiscal decentralization literature by extending the analysis of subnational taxation beyond revenue generation to include administrative capacity and governance effectiveness. It develops an integrated framework linking fiscal capacity and institutional factors in evaluating the opsen tax, while also providing practical insights for optimizing regional tax policy in Indonesia.